Secretory vesicle trafficking in awake and anaesthetized mice: differential speeds in axons versus synapses. (1st July 2018) - Knabbe, Johannes; Nassal, Joris Paul; Verhage, Matthijs; Kuner, Thomas
Abstract : Key points: Despite their immense physiological and pathophysiological importance, we know very little about the biology of dense core vesicle (DCV) trafficking in the intact mammalian brain. DCVs are transported at similar average speeds in the anaesthetized and awake mouse brain compared to neurons in culture, yet maximal speed and pausing fraction of transport were higher. Microtubule plus (+)‐end extension imaging visualized microtubular growth at 0.12 μm/s and revealed that DCVs were transported faster in the anterograde direction. DCV transport slowed down upon presynaptic bouton approach, possibly promoting synaptic localization and cargo release. Our work provides a basis to extrapolate DCV transport properties determined in cultured neurons to the intact mouse brain and reveals novel features such as slowing upon bouton approach and brain state‐dependent trafficking directionality. Abstract: Neuronal dense core vesicles (DCVs) transport many cargo molecules like neuropeptides and neurotrophins to their release sites in dendrites or axons. The transport properties of DCVs in axons of the intact mammalian brain are unknown. We used viral expression of a DCV cargo reporter (NPY‐Venus/Cherry) in the thalamus and two‐photon in vivo imaging to visualize axonal DCV trafficking in thalamocortical projections of anaesthetized and awake mice. We found an average speed of 1 μm/s, maximal speeds of up to 5 μm/s and a pausing fraction of ∼11%. Directionality of transport differed between anaesthetized and awake mice. In vivo microtubule +‐end extension imaging using MACF18‐GFP revealed microtubular growth at 0.12 μm/s and provided positive identification of antero‐ and retrograde axonal transport. Consistent with previous reports, anterograde transport was faster (∼2.1 μm/s) than retrograde transport (∼1.4 μm/s). In summary, DCVs are transported with faster maximal speeds and lower pausing fraction in vivo compared to previous results obtained in vitro . Finally, we found that DCVs slowed down upon presynaptic bouton approach. We propose that this mechanism promotes synaptic localization and cargo release. Key points: Despite their immense physiological and pathophysiological importance, we know very little about the biology of dense core vesicle (DCV) trafficking in the intact mammalian brain. DCVs are transported at similar average speeds in the anaesthetized and awake mouse brain compared to neurons in culture, yet maximal speed and pausing fraction of transport were higher. Microtubule plus (+)‐end extension imaging visualized microtubular growth at 0.12 μm/s and revealed that DCVs were transported faster in the anterograde direction. DCV transport slowed down upon presynaptic bouton approach, possibly promoting synaptic localization and cargo release. Our work provides a basis to extrapolate DCV transport properties determined in cultured neurons to the intact mouse brain and reveals novel features such as slowing upon bouton approach and brain state‐dependent trafficking directionality.